Oxidative 3,3,3-trifluoropropylation of arylaldehydes - Ikeda, Akari; Omote, Masaaki; Nomura, Shiho; Tanaka, Miyuu; Tarui, Atsushi; Sato, Kazuyuki; Ando, Akira (Beilstein Journal of Organic Chemistry, 2013)
A reaction between (E)-trimethyl(3,3,3-trifluoroprop-1-en-1-yl)silane (1) and arylaldehydes 2 was triggered by fluoride anions to afford aryl 3,3,3-trifluoropropyl ketones 3 in moderate to good yield. A mechanistic study of this reaction indicated that it occurred via an allyl alkoxide (4). A subsequent 1,3-proton shift of the benzylic proton of 4 forms 3. This reaction involves oxidative 3,3,3-trifluoropropylation of an arylaldehyde to afford 4,4,4-trifluoro-1-arylbutan-1-one.
Keywords: cesium fluoride; organo-fluorine; 1,3-proton shift; trifluoromethyl; 3,3,3-trifluoropropenyl